Elevated prenatal anti-Müllerian hormone reprograms the fetus and induces polycystic ovary syndrome in adulthood. (June 2018) - Tata, Brooke; Mimouni, Nour El Houda; Barbotin, Anne-Laure; Malone, Samuel; Loyens, Anne; Pigny, Pascal; Dewailly, Didier; Catteau-Jonard, Sophie; Sundström-Poromaa, Inger; Piltonen, Terhi; Dal Bello, Federica; Medana, Claudio; et al.
Abstract Polycystic ovary syndrome (PCOS) is the main cause of female infertility worldwide and corresponds with a high degree of comorbidities and economic burden. How PCOS is passed on from one generation to the next is not clear, but it may be a developmental condition. Most women with PCOS exhibit higher levels of circulating luteinizing hormone, suggestive of heightened gonadotropin-releasing hormone (GnRH) release, and anti-Müllerian hormone (AMH) as compared to healthy women. Excess AMH in utero may affect the development of the female fetus. However, as AMH levels drop during pregnancy in women with normal fertility, it was unclear whether their levels were also elevated in pregnant women with PCOS. Here we measured AMH in a cohort of pregnant women with PCOS and control pregnant women and found that AMH is significantly more elevated in the former group versus the latter. To determine whether the elevation of AMH during pregnancy in women with PCOS is a bystander effect or a driver of the condition in the offspring, we modeled our clinical findings by treating pregnant mice with AMH and followed the neuroendocrine phenotype of their female progeny postnatally. This treatment resulted in maternal neuroendocrine-driven testosterone excess and diminished placental metabolism of testosterone to estradiol, resulting in a masculinization of the exposed female fetus and a PCOS-like reproductive and neuroendocrine phenotype in adulthood. We found that the affected females had persistently hyperactivated GnRH neurons and that GnRH antagonist treatment in the adult female offspring restored their neuroendocrine phenotype to a normal state. These findings highlight a critical role for excess prenatal AMH exposure and subsequent aberrant GnRH receptor signaling in the neuroendocrine dysfunctions of PCOS, while offering a new potential therapeutic avenue to treat the condition during adulthood. Excess anti-Müllerian hormone during pregnancy results in polycystic ovary syndrome-like phenotypes in female offspring, possibly explaining its pathogenesis as well as suggesting a possible therapy.